NORMA-NORMA SOSIOKULTURAL PADA PENUTUR BAHASA BATAK TOBA DI KOTA JAMBI - Simarmata, Dicky Anthony Yohannes; Harahap, Eddy Pahar; Akbar, Oky; Akhyaruddin, Akhyaruddin; Purba, Andiopenta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This study aims to describe the sociocultural norms of interaction, interpretation and transformation in the culture of communication among Toba Batak speakers in Jambi City. This research was conducted in the city of Jambi, the source of the data in this study were the Toba Batak people who had settled in Jambi City and the Toba Batak people who lived within a certain time or had a certain limit. The approach taken is a qualitative approach with a descriptive research type. The data used in this study are in the form of fulfilling sociocultural and speech norms or conversations conducted by the Toba Batak language-speaking community, in the process of interaction and interpretation at the HKBP Agave church, traditional Toba Batak events, Toba Batak community organizations and Aur Duri Market. . Data collection techniques in this study used free speech, note-taking and record-keeping. The results of this study are to describe sociocultural norms of interaction, interpretation and cultural transformation in communication among Toba Batak speakers in Jambi City. Then the results of the researchers show that there are interacting sociocultural norms.